Age-associated declined function of endothelial progenitor cells and its correlation with plasma IL-18 or IL-23 concentrations in patients with ST-segment elevation myocardial infarction - Zhu, Yuanting; Cai, Guoyi; Lin, Luyang; Fu, Hongna; Zhang, Cong; Zeng, Lijin; Tu, Chang; Yang, Zhen (Frontiers in Cardiovascular Medicine, 2024)
Background ST-segment elevation myocardial infarction (STEMI) persists to be prevalent in the elderly with a dismal prognosis. The capacity of endothelial progenitor cells (EPCs) is reduced with aging. Nevertheless, the influence of aging on the functionality of EPCs in STEMI is not fully understood. Method This study enrolled 20 younger STEMI patients and 21 older STEMI patients. We assessed the Thrombolysis in Myocardial Infarction (TIMI) and Global Registry of Acute Coronary Events Risk (GRACE) scores in two groups. Then, we detected EPC migration, proliferation, adhesion, and plasma interleukin (IL)-18 and IL-23 concentrations in two groups. In addition, we analyzed the interconnection between age, EPC function, plasma IL-18 and IL-23 concentrations, and GRACE or TIMI scores in STEMI patients. Result GRACE and TIMI scores in older STEMI patients were higher than in younger STEMI patients, whereas EPC function declined. GRACE and TIMI scores were found to have an inverse relationship with the EPC function. In older STEMI patients, plasma concentrations of IL-18 and IL-23 increased. Plasma IL-18 and IL-23 concentrations were adversely connected to EPC capacity and positively related to GRACE and TIMI scores. Moreover, age was positively correlated with plasma IL-18 or IL-23 concentrations, as well as GRACE or TIMI scores. However, age was adversely correlated with EPC function. Conclusion In patients with STEMI, aging results in declined EPC function, which may be associated with inflammatory cytokines. The current investigation may offer new perception about mechanism and therapeutic targets of aging STEMI.